The demand of guava in Colombia - Alonso Cifuentes, Julio César; Ordóñez Morales, Pablo José; Rivera Triviño, Andrés Felipe (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
In Colombia, no systematic work have been carried out to determine the demand for fruits beyond descriptive analysis of per capita consumption according to different individual socioeconomic characteristics and much less for a specific product such as guava, Psidium guajava L. (Myrtaceae). This paper estimates the relationship between guava prices and the demand of guava in Colombia. We found that guava consumption is not affected by its price and its demand is highly correlated to income. While socio-economic characteristics such as income, education and household head labor affect the decision-making for consuming guava, other characteristics such as race and the number of household members determine the quantity of guava consumed in a Colombian household.